Design and Fabrication of Gallic Acid Loaded Chitosan Nanoformulation - Pathak, Kalyani; Das, Ratna J.; Saikia, Riya; Sahariah, Jon Jyoti; Pathak, Hemanta; Sarma, Himangshu; Das, Aparoop (Drug Delivery Letters, 2022)
Background: Gallic acid is a natural phenolic compound found in several fruits and medicinal plants. It is reported to have several health-promoting effects, including antioxidant, antiinflammatory, antidiabetic, and antineoplastic properties in gastrointestinal, neuropsychological, metabolic, and cardiovascular disorders. Aims: The aim of the present work was to study the influence of formulation factors on the physicochemical properties of gallic acid-loaded chitosan nanoparticles in order to optimize the formulation. Methods: Active chitosan nanoparticles could be used to support the modification of gallic acid delivery. The nanoparticles were prepared by the emulsification-solvent evaporation method using sonication. A 3-factor, 2-level BBD (Box-Behnken Design) was applied for exploring and optimizing the main effects, quadratic effects, as well as interaction effects of the ingredients of the formulation on the performance of the nanoparticles. The responses like particle size, polydispersity index, zeta potential, and encapsulation efficiency were also determined. Results: The concentration of gallic acid nanoparticles seems to be the most critical element affecting their properties. The concentration of chitosan was increased, which resulted in an increase in particle size. The optimised drug-loaded nanoparticles have a zeta potential of -5.2 mV due to their largely negative surface charge. Although the measured zeta potential was low, the nanoparticle dispersion remained stable, and no significant change in the shape or particle size of the gallic acidloaded chitosan nanoparticles was seen after two weeks at 4°C. The gallic acid-loaded nanoparticles have a particle size of 230 nm. Gallic acid reduced the particle size after it was added. One probable explanation for this is that the loaded medicine increased the cohesive force of the hydrophobic contact, resulting in the size reduction. A formulation was optimised based on the acquired results, and the experimental values were comparable to the expected values. FTIR examination revealed that gallic acid-loaded chitosan nanoparticles displayed both hydrogen bond and ionic interactions, allowing for active agent encapsulation and augmentation. Conclusion: The overall results indicated that by decreasing the chitosan concentration, drug entrapment efficiency increased and gallic acid concentration was the main factor influencing particle size, while entrapment efficiency was predominantly affected by the chitosan concentration.
Keywords: Nanoparticle